Perturbation of homogeneous thermal conductivity distribution in some carbonates by stylolites - Padmanabhan, Eswaran (2012)
Stylolites are partings within rocks that exhibit complex mutual column and socket interdigitization. These features can exhibit pronounced roughness on several scales. Stylolites, under deep-burial conditions, could permit circulation of undersaturated fluids and become reservoirs allowing also deep commercial gas production. However, the impact of stylolites on variations in thermal conductivity in carbonates is not well-known. This study was undertaken to investigate the heterogeneity in thermal conductivity in a variety of carbonate specimens containing different types of stylolites. A total of 9 carbonate samples from Turki were used in this study. These sampes were imported into Malaysia by a local factory. The stylolites were classified into three types. Type 1 (sharp-peak) has well defined and high density (4 amplitudes per cm) fractures. Type 2 (simple wave-like) is intermediate whereas type 3 (sutured) has poorly defined and low density (< 1 amplitude per cm) fractures. The thermal conductivity of type 2 (mean = 3.30 W m-1K-1) was the highest and that of type 3 (mean = 1.35 W m-1K-1) was lowest. Similar trends were recorded for non-stylolitic faces of the three carbonates specimens mentioned above. Faces with stylolites showed a high degree of variability in terms of thermal conductivity when estimated at various points. Surfaces with stylolites tend to show different thermal conductivity values than non-stylolitic faces. The reduction in porosity, type of stylolite and a possible effect of different orientation of the carbonate minerals in the stylolites, appears to perturb the homogeneous distribution of thermal conductivity in these carbonates. The study indicates that thermal conductivity estimation is point-dependant. The perturbations created by the stylolites would result in spatial variations in thermal conductivity with possible implications of differences in thermal maturation of hydrocarbon resources at the micro-site levels.